1987
DOI: 10.1016/0014-5793(87)81037-2
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5‐trisphosphate and 5′‐GTP induce calcium release from different intracellular pools

Abstract: It has been shown recently by several groups that 5'-GTP can release calcium from intraceilular compartments independently from inositol 1,4,5-trisphosphate (Ins(1,4,5)P3) by a mechanism which seems to be different from that used by Ins(1,4,5)P 3. We report here for the first time that the 5'-GTP-sensitive and the Ins(l,4,5)P3-sensitive calcium pools reside in different intracellular compartments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 12 publications
3
21
0
Order By: Relevance
“…In Swiss 3T3 fibroblasts, the bombesinor vasopressin-stimulated elevation of [Ca2+]i was mediated by an increase in the production of 1,4,5-InsP s, while the platelet-derived growth factor-induced eleva-tion of [Ca~+] i was not (Lopez-Rivas et al, 1987). Other reports demonstrated that (intracellular) GTP can release Ca 2+ from different intracellular pools insensitive to InsP 3 (Henne et al, 1987;Nicchitta et al, 1987;Benedetti et al, 1988), and that elevated concentrations of cytosolic Na + can exchange for mitochondrial Ca ~+. Similar pathways may be activated by ATP, although there is not yet any evidence for a specific mechanism.…”
Section: Extraceuular Ca 2+ Contributes To the Elevation Of [Ca2+]i Bmentioning
confidence: 96%
“…In Swiss 3T3 fibroblasts, the bombesinor vasopressin-stimulated elevation of [Ca2+]i was mediated by an increase in the production of 1,4,5-InsP s, while the platelet-derived growth factor-induced eleva-tion of [Ca~+] i was not (Lopez-Rivas et al, 1987). Other reports demonstrated that (intracellular) GTP can release Ca 2+ from different intracellular pools insensitive to InsP 3 (Henne et al, 1987;Nicchitta et al, 1987;Benedetti et al, 1988), and that elevated concentrations of cytosolic Na + can exchange for mitochondrial Ca ~+. Similar pathways may be activated by ATP, although there is not yet any evidence for a specific mechanism.…”
Section: Extraceuular Ca 2+ Contributes To the Elevation Of [Ca2+]i Bmentioning
confidence: 96%
“…Inositol trisphosphate is formed at the basolateral membrane by receptor-ligand activation of phospholipase C hydrolysis of phosphatidylinositol 4,5-bisphosphate (9,12,(36)(37)(38)(39)(40). In many cell types (41), including the parotid acinar cell (13,42), inositol trisphosphate-induced Ca2+ release is associated with a microsomal fraction enriched in endoplasmic reticulum markers. Whether the entire endoplasmic reticulum, only a specialized fraction of it (35,(42)(43)(44)(45)(46)(47), or another organelle (48) …”
Section: Methodsmentioning
confidence: 99%
“…In many cell types (41), including the parotid acinar cell (13,42), inositol trisphosphate-induced Ca2+ release is associated with a microsomal fraction enriched in endoplasmic reticulum markers. Whether the entire endoplasmic reticulum, only a specialized fraction of it (35,(42)(43)(44)(45)(46)(47), or another organelle (48) …”
Section: Methodsmentioning
confidence: 99%
“…the ER or selectively from one portion (Henne et al, 1987;Daniell and Harris, 1989;Ghosh et al, 1989;Burgoyne, et al, 1989), nor is it established whether the ER calcium pump is distributed uniformly or heterogeneously throughout the brain. Release of calcium by IP3 is mediated by a specific receptor protein which has been localized in the brain by autoradiography (Worley et al, 1987a(Worley et al, , 1989 and immunohistochemistry (Ross et al, 1989a), purified to homogeneity (Supattapone et al, 1988), molecularly cloned (Furuichi et al, 1989), and shown to comprise within a four-subunit 1000-kD protein both the IP3 recognition site and its associated calcium channel (Ferris et al, 1989).…”
Section: Introductionmentioning
confidence: 99%